Membangun Supremasi Dan Kesadaran Hukum Dalam Rangka Ketahanan Nasional - Nitibaskara, Tb. Ronny Rachman (Jurnal Kajian Stratejik Ketahanan Nasional, 2018)
Legal instruments are in the form of laws and regulations with the aim of regulating the life of a good and dignified society, nation and state by upholding justice through the rule of law. Law is the highest source (supremacy of law) in regulating and determining the mechanism of legal relations between the State and society as well as between members or groups of people with one another. the legal culture of each profession above has relevance to certain cultural dimensions. As quoted by Tamtelahitu and Tafakurrozak (2012). Edward T. Hall (1990) divides the cultural dimension. The research method used is a qualitative research method. The results of this study at this point finally emerge the feeling of law (rechtsgevoel), namely to see the law as a necessity so that law obedience flows without coercion. If the above reality continues to grow in society, a noble legal culture is born. Every party really permeates the prohibitions and dangers of actions that are prohibited by law, to finally be held firmly as the principle of life.